The use of neoadjuvant larotrectinib in the management of children with locally advanced TRK fusion sarcomas. Issue 21 (11th September 2018) - DuBois, Steven G.; Laetsch, Theodore W.; Federman, Noah; Turpin, Brian K.; Albert, Catherine M.; Nagasubramanian, Ramamoorthy; Anderson, Megan E.; Davis, Jessica L.; Qamoos, Hope E.; Reynolds, Mark E.; Cruickshank, Scott; Cox, Michael C.; et al.
Abstract: Background: The highly selective oral tropomyosin receptor kinase (TRK) inhibitor larotrectinib has demonstrated significant activity in adult and pediatric TRK fusion cancers. In the current study, the authors describe the clinical course of children with locally advanced TRK fusion sarcoma who were treated preoperatively with larotrectinib and underwent subsequent surgical resection. Methods: A total of 24 children were treated on a pediatric phase 1 trial of larotrectinib (ClinicalTrials.gov identifier NCT02637687). Five children who had a documented TRK fusion sarcoma and underwent surgical resection were included in the current analysis. Tumor response (Response Evaluation Criteria In Solid Tumors [RECIST] version 1.1) and surgical outcomes were collected prospectively. Results: A total of 5 patients (median age, 2 years; range, 0.4‐12 years) had locally advanced infantile fibrosarcoma (3 patients) or soft‐tissue sarcoma (2 patients). Four patients had disease that was refractory to standard therapy. All 5 patients achieved a partial response to larotrectinib by version 1.1 of RECIST and underwent surgical resection after a median of 6 cycles (range, 4‐9 cycles) of treatment. Surgical resections were R0 (negative resection margins with no tumor at the inked resection margin) in 3 patients, R1 (microscopic residual tumor at the resection margin) in 1 patient, and R2 (macroscopic residual tumor at the resection margin) in 1 patient. Three patients achieved complete (2 patients) or near‐complete (>98% treatment effect; 1 patient) pathologic responses. These patients remained in follow‐up and were no longer receiving larotrectinib for a minimum of 7 to 15 months postoperatively. Two patients had viable tumor at the time of surgical resection and positive resection margins and continued to receive adjuvant larotrectinib. No patients experienced postoperative complications or wound healing issues. Conclusions: Children with locally advanced TRK fusion sarcomas may proceed to surgical resection after treatment with the selective TRK inhibitor larotrectinib, thereby sparing them the potentially significant morbidity noted with current approaches. These results support the evaluation of larotrectinib as presurgical therapy in children with newly diagnosed TRK fusion sarcomas. Abstract : Children with locally advanced tropomyosin receptor kinase (TRK) fusion sarcomas may proceed to surgical resection after neoadjuvant treatment with the selective oral TRK inhibitor larotrectinib, sparing them the potentially significant morbidity noted with current approaches. The results of the current study support the further evaluation of larotrectinib as neoadjuvant therapy in children with newly diagnosed TRK fusion sarcomas.